The (Mis)Uses of Enchantment: Displacing the Authorities of Literary Criticism and Anthropology - Čale-Feldman, Lada (1998)
The text questions the efficacity of the use of literary texts for anthropological purposes, offers a brief overview of which situation has led to the interweaving of anthropology and literary theory and summarizes the author's own work on confronting plays and anthropological sources as often incommensurable documents which can offer some conclusions both for literary criticism and anthropology.